STRATEGIES FOR MODULATING THE RUMEN MICROBIOME TO IMPROVE TROPICAL CATTLE PRODUCTIVITY: A REVIEW ARTICLE - M. Dzikri Hudiatma; Ryzal Satria Aditama; Ana Fitria; Trisusanti; Irma; Fikya Juanda; Desima Natalia Harianja; Siti Resita Dijayanti (Journal of Animal Research and Applied Science, 2026)
Tropical cattle generally have lower productivity than subtropical cattle due to poor forage quality, high lignin content, heat stress, and inefficient ruminal nutrient utilization. The rumen microbiota, consisting of bacteria, archaea, protozoa, anaerobic fungi, and bacteriophages, plays a crucial role in feed fermentation, microbial protein synthesis, and volatile fatty acid production, which support animal growth and performance. This review aimed to summarize current strategies for rumen microbiome modulation to improve tropical cattle productivity. The novelty of this review lies in integrating various modulation approaches and evaluating their applicability under tropical conditions, particularly in Indonesian smallholder livestock systems and the utilization of locally available feed resources. A narrative review was conducted using 55 peer reviewed articles published between 2014 and 2025 from Scopus, ScienceDirect, Springer, MDPI, and Google Scholar. The findings identified four major microbiome modulation strategies: feed and additive modulation, supplementation with Direct Fed Microbials (DFM), partial defaunation using phytogenic compounds, and molecular approaches utilizing omics technologies and genetic engineering. Supplementation with *Saccharomyces cerevisiae*, *Lactobacillus* spp., and *Bacillus* spp. has been reported to improve fiber digestibility, average daily gain, and immune responses. Partial defaunation using local plants rich in tannins, saponins, and lipids can reduce methane emissions, although production responses vary. Omics technologies provide opportunities for precision interventions through the identification of target genes involved in methanogenesis and fiber degradation. Overall, integrating locally available feeds, feed additives, and microbial supplementation appears to be the most practical strategy for improving rumen efficiency and productivity in Indonesian tropical cattle, while omics technologies offer promising prospects for future precision livestock production.